Exploring of the gender variations in 4Cs skills among primary students - Azza Saad (18255742) (2024)
The development of 21st-century learning skills must prioritize collaborative problem-solving abilities. These include critical thinking, creativity, cooperation, and communication (4Cs) and the gender-based difference in the proficiencies of these skill have been reported in literature. The purpose of this study was to explore gender differences in 4Cs skills between males and females among the primary students after the execution of an informal program. This research provides an example of a STEM program that uses a problem-solving methodology to encourage students interested in environmental sustainability. The research was conducted with 43 female students and 93 male students. The study used a mixed-method involving qualitative observations of facilitators feedback, quantitative paired t-test and SWOT (strengths, weaknesses, opportunities and threats) analysis to evaluate students’ 4C skills. Results of the study revealed that there were statistically significant differences between males and females. The Shapiro-Wilk test for normality revealed that the data did not have a normal distribution, non-parametric analysis, such as the Mann Whitney U test, Spearman's Rho correlation were used. Findings from the Mann-Whitney U test illustrated that males received significantly greater mean score than females on the critical thinking and communications after the program. The females received more score than males on the collaboration and creativity (p < 0.05). The Spearman's Rho correlation analysis reveals that there is a positive correlation between students’ critical thinking and creativity (both male and Female) (p < 0.001). The development of advanced thinking abilities and creativity through facilitation is argued in this study. In summary, a strengths, weaknesses, opportunities, and threats (SWOT) analysis has demonstrated the effective use of the 4Cs skills throughout the duration of a week-long course. It, thus, can be concluded that the Integrated Problem-solving approach can be used as an alternative approach for empowerment of students’ 4Cs skills. Future research should look at the effects of participants' 4Cs on long-term development in formal education. Other Information Published in: Thinking Skills and Creativity License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.tsc.2024.101510